Settlement of Traffic Crimes Based on Restorative Justice (Study of Decision Number 125/Pid.Sus/2024/Pn Pso) - Maulana Arnivan Suaeri (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Traffic crimes are one of the most common forms of legal violations in everyday life. With increasing mobility and the growth of motorized vehicles, traffic violations have become an inevitable phenomenon in almost every city in Indonesia. These violations include various forms, ranging from administrative violations to criminal acts such as driving without a license, running red lights, and traffic accidents due to negligence. In many cases, traffic crimes not only harm the state and other road users, but can also result in injuries and even death. Law Number 22 of 2009 concerning Traffic and Road Transportation has regulated criminal sanctions for traffic violators. However, the law enforcement approach used so far tends to be repressive and retributive. The legal process for traffic violations is generally pursued through formal litigation in court, which in practice requires considerable time, effort, and resources. Litigation often results in criminal penalties, even in cases that could actually be resolved through deliberation between the perpetrator and the victim. This raises serious issues regarding the effectiveness and efficiency of the criminal justice system in handling cases that actually have the urgency of social recovery rather than mere punishment. The application of formal and bureaucratic legal processes to traffic crimes, which often involve elements of negligence or accident, often leads to dissatisfaction among perpetrators, victims, and the wider community. The lengthy and convoluted legal process, which generally involves formal litigation in court, often feels burdensome for the parties involved. While perpetrators may feel that their actions were not malicious, victims feel that legal resolutions that focus solely on the criminal aspect have not fully repaired the losses they have experienced, and the wider community feels that this protracted justice system does not fully resolve the problem. Criminal law that focuses on sanctions and punishment does not always meet the expectations of a more humane and contextual justice in each criminal case. Most traffic crimes, especially those that occur due to negligence or minor errors, are actually better resolved through an approach that is oriented not only toward punishment but also toward restoring social relationships damaged by the incident. A criminal justice system that emphasizes punishment often neglects broader humanitarian aspects, such as emotional and social recovery between perpetrators and victims. In certain cases, both victims and perpetrators have reached amicable agreements, yet the legal process continues without considering these outcomes. This demonstrates a disparity between the goals of the criminal justice system, which should be oriented towards achieving comprehensive justice for victims, perpetrators, and society, and the reality on the ground, which prioritizes proving guilt and imposing punishment. In many cases, the primary focus of the conventional justice system is on the punishment imposed on perpetrators as a form of deterrence, without considering the importance of victim protection and recovery, as well as the perpetrator's reintegration into society.